Hybrid carbon dot assembly as a reactive oxygen species nanogenerator for ultrasound-assisted tumor ablation - Jana, Deblin (2022)
The efficacy of reactive oxygen species (ROS)-based therapy is substantially constrained by the limited ROS generation, stern activation conditions, and lack of a straightforward reaction paradigm. Carbon dots (CDs) have been highly sought after for therapeutic applications for their biocompatibility and intrinsic fluorescence imaging capabilities, making them suitable for ROS generation. Herein, we synthesized a CD-based ultrasmall hybrid nanostructure possessing active sites of Mo, Cu, and IR-780 dye. After cooperative self-assembly with 1,2-distearoyl-sn-glycero-3-phosphoethanolamine-poly(ethylene glycol), the obtained assembly (CMIR-CDa) exhibits near-infrared fluorescence imaging and photoacoustic tomography. Interestingly, CMIR-CDa can generate singlet oxygen (1O2), hydroxyl radical (·OH), and superoxide radical anion (O2 • -) upon ultrasound stimulus owing to its sonosensitizing and enzyme-mimicking properties, showing an enhanced efficacy for tumor ablation in vivo. The collective in vitro and in vivo results indicate that CMIR-CDa has a high potency as an ROS nanogenerator under US irradiation, even at a low concentration. The present study offers an approach for engineering hybrid CDs in a bioinspired way for intratumoral ROS augmentation in response to deep tissue penetrable external stimuli.